IN THE CONTEXT OF GURU-DISCIPLE TRADITION VERSUS DISTANCE EDUCATION KATHAK DANCE: गुरू-शिष्य परम्परा बनाम दूरस्थ शिक्षा कथक नृत्य के संदर्भ में - Vaidya, Priyanka (International Journal of Research -GRANTHAALAYAH, 2015)
This verse depicts Guru's place in Indian philosophy, culture and tradition. In each of our Yajna sacrifices, in every puja this shloka is spoken. Does it not show the Guru's place in our life? Man has been accepted in Indian philosophy in a coordinated way of karma and knowledge. These two forms only lead him in gaining recognition and prestige in the society. Parents are factors for giving birth to a human being, but the wisdom of wisdom, knowledge and action is attained only by the Guru. Today's generation is forgetting the importance of Guru in the light of new knowledge, which is scientific knowledge, obtained by computer and Internet. But behind all this, man's knowledge, his ability is there, and he is the teacher to make him aware of this knowledge and ability. Only by the knowledge and ability provided by the Guru, a person makes his life happy and prosperous. The way Kabirdas has said यह ष्लोक भारतीय दर्षन, 8व परम्परा में गुरू के स्थान को दर्षाता है। हमारी प्रत्येक यज्ञ आहुति में, हर पूजा में इस ष्लोक को बोला जाता है। क्या यह हमारे जीवन में गुरू के स्थान को नहीं दर्षाता? भारतीय दर्षन में मनुष्य को कर्म और ज्ञान के समन्वित रूप से ही स्वीकार किया गया है। उसके ये दो रूप ही उसे समाज में पहचान एवं प्रतिष्ठा प्राप्त करने में मार्ग प्रषस्त करते हैं। माता-पिता मनुष्य को जन्म देने के कारक हैं, परन्तु बुद्धि, ज्ञान व कर्म का प्रकाष गुरू के द्वारा ही मनुष्य को प्राप्त होता है। आज की पीढ़ी नये ज्ञान के प्रकाष में जो कि वैज्ञानिक ज्ञान है, कम्प्यूटर द्वारा एवं इंटरनेट द्वारा प्राप्त है, को सम्पूर्ण मान गुरू की महत्ता को भूलती जा रही है। परंतु इस सब के पीछे भी मनुष्य का ज्ञान, उसकी योग्यता है और इस ज्ञान और योग्यता से उसको परिचित कराने वाला गुरू ही है। गुरू के द्वारा प्रदत्त ज्ञान और योग्यता से ही मनुष्य अपने जीवन को सुखमय और सम्पन्न बनाता है। जिस प्रकार से कबीरदास जी ने कहा ह